Reinfecciones por SARS-CoV-2 durante la segunda ola pandémica en Iquitos, Perú - Pampa-Espinoza, Luis Fernando; Padilla-Rojas, Carlos; Jiménez-Vásquez, Víctor; Silva, Iris; Díaz-Soria, Fabiola; Villa-Galarce, Zaira Hellen (Revista del Cuerpo Médico Hospital Nacional Almanzor Aguinaga Asenjo, 2022)
Carta al Editor (sin resumen)